Removal of arsenic from aqueous solution by various natural soil-based adsorbents - Fairuz, Farah Shahirah Mohd (2023)
Rapid industrialization, mining and agricultural activities lead to the release of contaminants such as arsenic (As) into the water sources that causes adverse effect to living organism. Thus, the application of effective and efficient removal method is crucial. The objective of the study is to apply the adsorption method by utilizing natural soil-based adsorbents including red, clay, sandy and black soil for removal of arsenic from aqueous solution. This study involved the characterisation of heavy metal content and physicochemical characteristic of soil adsorbents, followed by batch adsorption process and the study of adsorption model and mechanism. The results for concentration of arsenic in all soil adsorbents were lower than the permissible limit stated by European United (EU) and mean concentration of iron (Fe) observed to be higher in red soil compared to in other soil samples. For the physicochemical characterisation analysis, red soil has highest number of functional group, content of Fe based minerals, surface area and pore volume with the smallest particle size. From this study, the optimum removal conditions of arsenic from aqueous solution were 2.2 g/50 mL dosage of adsorbents for 60 minutes of contact time at pH of 5.5±0.5 and temperature of 40°C. The adsorption capability and efficiency of soil adsorbent in removing arsenic from aqueous solution were red soil> clay soil> sandy soil> black soil. The kinetic, isotherm and thermodynamic model showed that the mechanism of adsorption of arsenic was a chemisorption, non-spontaneous and endothermic process.